The Deep South Portuguese Margin: An Attempt to Account for Heat Flow Density Variation in this Region. - Duque, Maria Rosa (2022)
Heat flow data measured in a region characterized by a very high and non-uniform thickness (accretionary prism) of sediments, traversed by strike-slip faults in the E-W direction and thrust faults in the N-S direction, were analyzed. Mud volcanoes have been discovered in the region during the last 20 years. The region includes parts of the borders between the Eurasian and the African plates, at SW of the Iberian Peninsula. Sediment porosity and vertical fluid movements were inferred from thermal conductivity and thermal gradient data. Fault location and boundary of the sediment prism were used to test the results inferred and to explain the scatter in the published heat flow values. Special attention was given to values obtained in regions separating different geologic settings(Gorringe Bank – Horseshoe Plain and Marquês de Pombal fault region). Geoid height values were used to obtain information related with heat flow values from deep parts of the Horseshoe plain and in the Gorringe Bank located in the western part of the region studied outside the accretionary prism of sediments. Information related with the evolution of some transient properties in the region were obtained from geoid height variations using three models made for three different years. Information about the thermal disturbance caused by fluid movements in the region and the heat flow values without them were obtained at the end of the work.